Pelatihan Kewirausahaan Sebagai Upaya Meningkatkan Ekonomi Keluarga Kader ‘Aisyiyah Pimpinan Ranting Tanjung Selamat - Mavianti, Mavianti; Harfiani, Rizka; Rudi Setiawan, Hasrian (Maslahah: Jurnal Pengabdian Masyarakat, 2020)
Entrepreneurship training as an effort to improve the economy of the ‘Aisyiyah cadre family was conducted at the Branch Leader‘ Aisyiyah Tanjung Selamat. Along with the increasing economic needs, the mother as a cadre ‘Aisyiyah has a role to be able to help meet the needs of the family. The purpose of this service is to provide entrepreneurial skills for the Aisyiyah cadres. The method used is an interactive discussion, training or counseling as well as conducting practicum by inviting cadres of women isy Aisyiyah for entrepreneurial practices such as making handicrafts and food preparations. The result of this dedication is the increased motivation of cadres isy Aisyiyah to improve skills in order to help the family economy. With the economic growth of cadre family ‘Aisyiyah, it will sustain the economy of the Branch Leader‘ Aisyiyah Tanjung Selamat. Keywords : Entrepreneurship Training